TRANSPORT AND TRANSFORMATION OF CHEMICAL COMPONENTS IN THE GROUNDWATER FLOW SYSTEM OF JAKARTA METROPOLITAN AREA - Mitsuyo Saito; Shin-ichi Onodera; Yu Umezawa; Takahiro Hosono; Yuta Shimizu; Robert M. Delinom; Rachmat Fajar Lubis; Makoto Taniguchi (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2011)
ABSTRACT The aim of this study is to examine the transport and transformation of chemical components within the groundwater flow in Jakarta area, and to evaluate the effects of accelerated urbanization on it. The collected data showed that the current hydraulic potential in the Jakarta metropolitan area is below sea level because of prior excess abstraction of groundwater. The distribution of Cl- and Mn2- concentration in groundwater suggests that the decline in hydraulic potential has caused the intrusion of seawater to shallow groundwater and the movement of shallow groundwater into deep groundwater. It implies an accumulation of contaminants in deep aquifers. On the other hands, the presentation of NO3--N in groundwater is suggested to be attenuated by the processes of denitrification and dilution in the coastal area.